1974
DOI: 10.1103/physrevlett.32.1098
|View full text |Cite
|
Sign up to set email alerts
|

Profound Effect of a Magnetic Field on the Phase Diagram of SuperfluidHe3

Abstract: In the presence of a magnetic field the 3 He A phase is interposed between the normal liquid and the 3 He B phase for all pressures measured, including pressures below that of the polycritical point. This can be understood on the basis of known nuclear paramagnetic properties if at a given pressure both 3 He A and 3 He B have the same critical temperature and if there are plausible small differences in the heat capacties of the two phases.We have discovered that a rather weak magnetic field acting on the weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 10 publications
3
44
0
Order By: Relevance
“…9. If V0 is the liquid 3He sample volume on reaching the melting curve, then the number of moles of 3He in the cell was n3 = VolOt (5) where vt = 25.62111 + (33.662-P0)xd cm3/mole…”
Section: Measurement Of Volumementioning
confidence: 99%
See 1 more Smart Citation
“…9. If V0 is the liquid 3He sample volume on reaching the melting curve, then the number of moles of 3He in the cell was n3 = VolOt (5) where vt = 25.62111 + (33.662-P0)xd cm3/mole…”
Section: Measurement Of Volumementioning
confidence: 99%
“…1-3 In this paper we give a complete description of this work with particular emphasis on experimental detail. 5 Their work, combined with that of Ahonen et al, 6 establishes the phase diagram at pressure less than 34 bar. The P = 0 value of Tc is attributable to Ahonen et al 6 The effect upon TAB of a 378-Oe magnetic field is shown by the 9 5 9 . dashed hne.…”
Section: Introductionmentioning
confidence: 99%
“…For the calculation of the normalized spin susceptibility in the BW state we use Eqs. (16), (17), (5), (6), and (9). Our theoretical results for P = l 0, 20, and 30 bar are shown in Fig.…”
Section: Superfluid Densitymentioning
confidence: 99%
“…Both these measurements were done on the melting curve. Paul son, Kojima, and Wheatley (10) found that in a field of 30 -4 0 mT (300 -400 gauss) a narrow tail of the A-phase extends between the normal Fermiliquid and the B-phase down to 10 bar at least.…”
mentioning
confidence: 97%
“…In this paper I shall first describe several experimental facts about liquid (6) (7) (10). Note the logarithmic temperature scale.…”
mentioning
confidence: 99%